DASAR PEMBAGIAN KEWENANGAN NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM BIDANG PERTANAHAN - I Wayan Eka Darma Putra (RechtIdee, 2018)
This study aims to analyze the basis for authority division of notary and Official Certifer of Title Deed in land sector and to examine whether Article 15 Paragraph 2 letter (f) of Law Number 2 year 2014 concerning notary is contrary to Article 2 of Government Regulation Number 37 year 1998 on the rule of position for Official Certifer of Title Deed. This research is legal research normative by design with statute and historical approaches employed. The legal materials obtained were analized and assessed to reveal the correlation between them. The findings of the study show that the authority of the notary comes from Notary Regulation (Stb. 1860 : 3) and the authority of the Official Certifer of Title Deed is generated from Government Regulation number 37 year 1998 on the rule of position for Official Certifer of Title Deed. Article 15 paragraph (2) letter (f) about notary position does not contradict Article 2 of Government Regulation number 37 year 1998 because the land deed such as lease deed, sale and purchase agreement, deed of land right release, the authority to sell, statement of inheritance, will, and deed of grant of mortgage is the authority of the notary and not the Official Certifer of Title Deed.